The future of business and industrial marketing and needed research - Wesley J. Johnston (jbm - Journal of Business Market Management, 2014)
There are usually no shortages of predictions of what the future will be like. In fact life would be impossible without them. We predict that tomorrow will be similar to today and that our students or customers will still need what we have to offer. That our car will start or the bus will be there at the usual time. The building we work in will still be standing and the visual recognition software will open our office door. It is only when we start to look further into the future that our predictions become less certain. Two recent predictions of the future of marketing serve as interesting examples.
urn:nbn:de:0114-jbm-v7i1.866
Keywords: 650